Designable Layer Edge States in Quasi‐2D Perovskites Induced by Femtosecond Pulse Laser. Issue 20 (12th May 2022) - Miao, Yu; Xiao, Zeqi; Zheng, Zeyu; Lyu, Da; Liu, Qin; Wu, Jieyu; Wu, Yongbo; Wen, Xiewen; Shui, Lingling; Hu, Xiaowen; Wang, Kai; Tang, Zhilie; et al.
Abstract: The low‐energy layer edge states (LESs) from quasi 2D hybrid perovskite single crystals have shown great potential because of their nontrivial photoelectrical properties. However, the underlying formation mechanism of the LESs still remains controversial. Also, the presence or creation of the LESs is of high randomness due to the lack of proper techniques to manually generate these LESs. Herein, using a single crystals platform of quasi‐2D (BA)2 (MA)n−1 Pbn I3n+1 ( n > 1) perovskites, the femtosecond laser ablation approach to design and write the LESs with a high spatial resolution is reported. Fundamentally, these LESs are of smaller bandgap 3D MAPbI3 nanocrystals which are formed by the laser‐induced BA escaping from the lattice and thus the lattice shrinkage from quasi‐2D to 3D structures. Furthermore, by covering the crystal with tape, an additional high‐energy emission state corresponding to the reformation of (BA)2 PbI4 ( n = 1) within the irradiation region is generated. This work presents a simple and efficient protocol to manually write LESs on single crystals and thus lays the foundation for utilizing these LESs to further enhance the performance of future photoelectronic devices. Abstract : Femtosecond laser ablation is proposed to write the layer edge states (LESs) with high spatial resolution and preciseness in quasi 2D perovskites. These low‐energy LESs are MAPbI3 nanocrystals formed by laser induced BA escaping from the lattice and the lattice shrinkage. Sealing of the irradiated film can further induce additional high‐energy states by the formation of (BA)2 PbI4 .